A hermeneutic of intercultural learning: The writings of John Colenso - Mitchell, Gordon (Old Testament essays, 1997)
Colenso arrived in Africa convinced that the purest religious Truth was to be found in a human conscience unsullied by dogma. The African people and the ancient Israelites shared a universal religion. He therefore consciously uses his own exposure to cultural diversity as the key to Biblical hermeneutics. Observations made by William Ngidi, who assisted in the translation of the Pentateuch, are recorded in the commentaries as the touchstone of Truth. Cynics point out that Ngidi functions in Colenso's writings as little more than the spokesperson for the Bishop's own opinions. This in no sense diminishes the importance of his appreciation for the cross-cultural reading of the Bible and his spirited defence of the role of the ordinary reader.